Physiological potential of corn seeds treated with different dosages of molybdenum and potassium - Gomes, Gisely Paula; Queiroz, Robison Alesandro de; Takahashi, Lúcia Sadayo Assari (Semina: Ciências Agrárias, 2021)
Corn is important in agriculture for its dual is uses as food and animal feed. The use of quality seeds is fundamental for outcomes in the field. The treatment of seeds with molybdenum may increase the productive capacity and uniformity of the corn. For this to work, the amount applied to the seeds must be adequate to promote development and increase the final crop production. Thus, the objective of this work was to verify the effects of molybdenum and potassium application on the germination and vigor of corn seeds. The physiological quality of the seeds was evaluated by germination, first count, seedling length (shoot and root), seedling dry matter mass, emergence, and the cold test. Six treatments (T1-T6) were performed, with T1 free of molybdenum and potassium and the others with varying dosages. The seeds were treated with a commercial product that containing molybdenum and potassium. The design was completely randomized, with four replications and six treatments. Smaller doses of molybdenum resulted in a higher percentage of normal seedlings. Based on the length and dry mass of the seedlings, it was verified that maize seeds were negatively impacted by increasing doses of molybdenum and potassium. In the emergence tests in sand, treatments T5 and T6 presented a greater number of seedlings. The physiological quality of corn seeds was not significantly influenced by the application of molybdenum and potassium in the first count and germination results in the cold and germination tests.